2019
DOI: 10.1055/s-0039-1693033
|View full text |Cite
|
Sign up to set email alerts
|

All I Have Learned, I Have Learned from Google: Why Today's Facial Rejuvenation Patients are Prone to Misinformation, and the Steps We can take to Contend with Unreliable Information

Abstract: A growing number of patients are seeking answers for their health concerns online. This study assesses the reliability, quality, and readability of online materials patients have access to through the Internet and evaluates the social media presence of information providers. An online search was conducted for facial rejuvenation by utilizing three ubiquitously used web search engines: Google, Bing, and Yahoo. The first 25 result pages were collected from each search engine, and exclusionary criteria were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Database search and review of article references revealed 46 eligible articles for inclusion in this scoping review (Table 1). 8,10–54 These articles represented the spectrum of plastic surgery, including breast (22%), facial aesthetics (17%), general plastic surgery (13%), hand surgery (15%), f (9%), craniofacial (9%), lymphedema (7%), gender affirmation surgery (4%), lower extremity reconstruction (2%), and vascularized composite allotransplantation (2%) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Database search and review of article references revealed 46 eligible articles for inclusion in this scoping review (Table 1). 8,10–54 These articles represented the spectrum of plastic surgery, including breast (22%), facial aesthetics (17%), general plastic surgery (13%), hand surgery (15%), f (9%), craniofacial (9%), lymphedema (7%), gender affirmation surgery (4%), lower extremity reconstruction (2%), and vascularized composite allotransplantation (2%) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In this scoping review, the 36 articles that assessed the readability of plastic surgery internet-based resources utilizing these tools demonstrated a mean reading grade level consistently higher than the eighth grade, regardless of the sub topic analyzed (Table 2). 8,10–44…”
Section: Resultsmentioning
confidence: 99%
“…With the development of evidence-based nursing which has higher requirements for literature index and retrieval [45], it is necessary for nurses to master good literature retrieval ability to carry out evidence-based nursing in clinical work [22]. Application of information index is one of the important ability of nurses' information literacy, through which nurses can learn the latest frontier dynamic knowledge in professional eld [46,47]. Therefore, nurses themselves should strengthen professional learning and skills development, and constantly improve the level of information literacy.…”
Section: Discussionmentioning
confidence: 99%
“…While some online resources are reliable and serve to empower patients, intermixed among them are concepts that are inaccurate, outdated, or unrealistic [ 2 , 4 , 5 ]. Recognizing dependable resources and deciphering complex medical information can be challenging, particularly in patients with limited health literacy (HL) [ 6 ]. HL represents the ability to comprehend health information and utilize it to make appropriate medical decisions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEMs above the ninth-grade level are considered difficult to read for an average adult [ 11 , 12 ]. Several studies in the current literature concluded that online plastic surgery PEMs are of low quality and written at unacceptably high reading levels [ 6 , 13 , 14 ]. Research investigating the quality and readability of PEMs specific to the field of oculofacial plastic surgery is sparse.…”
Section: Introductionmentioning
confidence: 99%